STUDI ERGONOMI TERHADAP POSTUR, BEBAN KERJA, DAN FAKTOR LINGKUNGAN PADA PETANI TOMAT: LITETRATUR REVIEW - Rizka Rizka Annisa; Fithri Handayani Lubis; Herlina J. EL-Matury; Pitto Pratiwi Malau (Jurnal Penelitian Kesmasy, 2025)
Tomato cultivation is an intensive agricultural activity that demands high physical exertion and exposes workers to considerable ergonomic and environmental risks. Most cultivation processes including planting, maintenance, and harvesting are still performed manually, often involving prolonged bending, squatting, and static standing postures. These conditions substantially increase the risk of work-related musculoskeletal disorders (MSDs). This literature review aims to integrate recent findings on the interrelationships among working posture, physiological workload, and environmental factors affecting the health and productivity of tomato farmers. The synthesis revealed a high prevalence of MSDs among agricultural workers, particularly affecting the lower back, neck, and shoulders, primarily due to repetitive and static working postures (Widyanti, 2018; Akbar et al., 2023). Physiological workload studies demonstrated that workers in greenhouse environments experienced elevated body temperatures and fatigue correlated with work intensity and ambient heat (Silalahi et al., 2017; Jung & Kim, 2022). Environmental stressors especially heat and humidity further exacerbate these conditions, leading to heat stress that compromises physical performance and health (FAO, 2018; El Khayat et al., 2022). Furthermore, improper postures during manual harvesting negatively affect both worker well-being and tomato fruit quality, whereas ergonomic practices enhance both efficiency and yield quality (Kuta et al., 2023). Recommended interventions include improved tool and workplace design, task rotation, adequate ventilation and shaded rest areas, and training on ergonomic harvesting techniques (FAO, 2018; Ahamed et al., 2023). The review also highlights research gaps, notably the lack of longitudinal studies and intervention evaluations within smallholder tropical farming contexts. Future research should adopt mixed-method approaches combining physiological, postural, and environmental assessments to develop sustainable, safe, and efficient agricultural work systems.